INFECTIOUS DISEASES IN CHILDREN UNDER TEN YEARS OLD AND THEIR PROPHYLAXIS - Magzumov Xamidulla Bashirovich (Western European Studies, 2025)
This article highlights common infectious diseases among children, their types, and their impact on health. It emphasizes that infections can progress rapidly and severely in children due to their fully undeveloped immune system. Furthermore, the article points out the significance of measures such as vaccination, adherence to sanitary and hygienic rules, conducting public health promotion, and early diagnosis of infections in preventing infectious diseases. In conclusion, it is stated that preventive measures are of crucial importance in preventing and reducing infectious diseases in children
Keywords: Children; infectious diseases; viral infections